OUTCOME OF PRIMARY TOTAL KNEE ARTHROPLASTY AMONG PATIENTS WITH MORBID OBESITY - SARDAR , SB; KHAN , A; FAZLANI , N; SAEED , FUR; RAHIM , IU; FAROOQ , OK (Biological and Clinical Sciences Research Journal, 2023)
This retrospective observational study aimed to assess the outcome of primary total knee arthroplasty among patients with morbid obesity. This retrospective observational study was conducted at the Department of Orthopaedic, Khyber Teaching Hospital Peshawar, from August 2021 to June 2023. We assessed the records of 120 morbidly obese patients who underwent total knee arthroplasty. The outcomes of total knee arthroplasty of morbidly obese patients were evaluated. Paired samples T-test was used to assess the knee society clinical and functional score of the patients. The mean age of 120 morbidly obese patients was 62.21±7.0. Gender-wise, Females were greater in number as compared to male patients (66.7% vs. 33.3%). The mean preoperative clinical KSS was 48.69±2.45 while the postoperative clinical KSS was 83.34±1.04 (P = 0.0001), the mean preoperative functional KSS was 43.69±1.73, and the postoperative functional KSS was 70.03±3.31 (P = 0.0001). We conclude that total knee arthroplasty in morbidly obese patients resulted in significantly better outcomes in terms of clinical and functional knee scores.